Multifield Coupling Mechanism of Unloading Deformation and Fracture of Composite Coal-Rock - Zhen Yang; Yan Li; Xin Li; Jiayu Zhuang; Hao Li; Xue Wang; Yuning Wang (Shock and Vibration)
The deformation and fracture evolution of coal and rock under unloading are prone to sudden instability or dynamic damage. To solve the problem, this paper combines interdisciplinary theories such as damage mechanics and electromagnetic field theory. The mathematical model of multiphysics coupling during loading and unloading of composite coal-rock is deduced. In addition, numerical simulations along with experimental verification are carried out to study multi-physical field variation and coupling mechanisms. The composite coal-rock deforms and ruptures under unloading, and the brittle failure of the rock body becomes more sudden when the confining pressure is unloaded. Macroscopically, many microcracks are generated and expanded during the loading and unloading of composite coal-rock. Microscopically, the internal old molecular chains are broken to form new molecular chains by the force. Simulation results show that, during the loading and unloading process, the three physical fields of the composite coal-rock all change regularly. During the unloading of coal and rock, there is a transition period in which the temperature increases sharply and reaches the maximum. Then, the temperature decreases due to the gradual decrease of its bearing capacity. Besides, the electromagnetic field is strongest on the surface of the coal body, and its propagation in the air decays exponentially. There are small fluctuations that appear at the junction of the coal body and the air. The experimental results show that the internal infrared radiation temperature of the composite coal-rock decreases during the initial stage of loading and unloading due to the discharge of internal gas. In the first stage of “loading and unloading,” it increases with the increase in stress, and the temperature suddenly increases in a short time after unloading. The electromagnetic radiation fluctuates in small amplitudes at the initial stage. When the stress is about to reach the peak, the electromagnetic radiation intensity increases and reaches the peak suddenly. Then, the coal-rock ruptures, the stress decreases, and the electromagnetic radiation weakens. The experiment and simulation results are consistent. The multiphysics coupling model is used to study the characteristics of coal and rock unloading under complex conditions, providing a theoretical basis and new method for the prediction and forecast of coal and rock mining dynamic disasters.